2021
DOI: 10.31234/osf.io/bdcga
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

But What’s Your Partner up to? Associations between Relationship Quality and Pornography Use Depend on Contextual Patterns of Use within the Couple

Abstract: It is commonly assumed that pornography use harms relationships. In the current research, we contribute to a small but growing body of work that challenges this assumption by examining an alternative explanatory mechanism for the associations between pornography use and relationship dysfunction. In contrast to dominant exposure-based explanations in this field, we argue instead that the apparent negative “impact” of pornography use on relationship quality may be the product of partner similarity or differences… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 60 publications
0
1
0
Order By: Relevance
“…Another study suggests not only that partners tend to be similar in their levels of erotophobia-erotophilia, but that individuals with higher levels of erotophilia can better estimate their partner's sexual satisfaction (Smith et al, 1993). Similarly, other findings in this area have indicated that couple members who both hold more erotophilic attitudes are more likely to have concordant solitary or shared pornography use, which has been shown to correlate positively with interpersonal closeness, comfort with sexual communication, and sexual satisfaction (Kohut et al, 2018;Kohut et al, 2021).Moreover, as sexual and relationship satisfaction are known to be highly correlated (Wincze & Carey, 2001;Byres, 2005), it can be suggested that the knowledge of compatibility in sexual attitudes and practices can be an influential factor in promoting and assessing healthier and more harmonious relationships by therapist and counsellors.…”
Section: Results Of Thementioning
confidence: 93%
“…Another study suggests not only that partners tend to be similar in their levels of erotophobia-erotophilia, but that individuals with higher levels of erotophilia can better estimate their partner's sexual satisfaction (Smith et al, 1993). Similarly, other findings in this area have indicated that couple members who both hold more erotophilic attitudes are more likely to have concordant solitary or shared pornography use, which has been shown to correlate positively with interpersonal closeness, comfort with sexual communication, and sexual satisfaction (Kohut et al, 2018;Kohut et al, 2021).Moreover, as sexual and relationship satisfaction are known to be highly correlated (Wincze & Carey, 2001;Byres, 2005), it can be suggested that the knowledge of compatibility in sexual attitudes and practices can be an influential factor in promoting and assessing healthier and more harmonious relationships by therapist and counsellors.…”
Section: Results Of Thementioning
confidence: 93%
“…While relatively scant, existing research indicates sexual experimentation with shared pornography use, new sexual positions, and the use of sex toys are relatively common among couples (Herbenick et al, 2009;Kohut et al, 2017;Lehmiller et al, 2020;Reece et al, 2009), and that partners who engage in such behaviors together report higher closeness, greater ease in sexual communication, and high sexual and relationship satisfaction (Frederick et al, 2017;Kohut et al, 2018;Lehmiller et al, 2020).…”
Section: Novel Sexual Behavior and Relationship Quality In Long-term ...mentioning
confidence: 99%